2019
DOI: 10.1007/s00334-018-0708-5
|View full text |Cite
|
Sign up to set email alerts
|

What can crop stable isotopes ever do for us? An experimental perspective on using cereal carbon stable isotope values for reconstructing water availability in semi-arid and arid environments

Abstract: This study reassesses and refines the use of crop carbon stable isotope values (Δ 13 C) to reconstruct past water availability. Triticum turgidum ssp. durum (durum wheat), Hordeum vulgare (six-row barley) and Sorghum bicolor (sorghum) were experimentally grown at three crop research stations in Jordan for up to three years under five different irrigation regimes: 0% (rainfall only), 40%, 80%, 100% and 120% of the crops' optimum water requirements. The results show a large variation in carbon stable isotope val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 62 publications
2
22
1
Order By: Relevance
“…Given the substantial differences in the regional climate, environment, soil conditions and ancient wheat varieties, estimates of the water supply by using the carbon isotope composition of ancient wheat grains likely contain errors (Flohr et al, 2019). However, the effect of C isotope fractionation due to the difference of water supply is more obvious, the overall linear correlation between the water supply and wheat grain Δ values is very clear (Araus et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the substantial differences in the regional climate, environment, soil conditions and ancient wheat varieties, estimates of the water supply by using the carbon isotope composition of ancient wheat grains likely contain errors (Flohr et al, 2019). However, the effect of C isotope fractionation due to the difference of water supply is more obvious, the overall linear correlation between the water supply and wheat grain Δ values is very clear (Araus et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Theoretically, since plants assimilate atmospheric CO 2 , they discriminate against heavier 13 C isotopes, which are less prevalent in the atmosphere. Studies have shown that the degree of 13 C depletion is greater when plants keep their stomata open for a longer period of time (Araus et al, 2014; Farquhar and Richards, 1984; Flohr et al, 2019; Wallace et al, 2013, 2015). Opening the stomata allows a plant to respirate, engage in photosynthesis, cool its temperature, and ensure its nutrient uptake; however, it also causes greater transevaporation, dehydrating the plant.…”
Section: Introductionmentioning
confidence: 99%
“…Stable carbon isotope analysis of crop remains is becoming increasingly popular as a means of reconstructing past plant water availability. In archaeology, it has gained particular interest as a crop water status proxy and/or for elucidating past water management regimes (Aguilera et al, 2011; Araus et al, 2014; Flohr et al, 2019; Riehl et al, 2008, 2014; Styring et al, 2016; Vaiglova et al, 2014; Wallace et al, 2015). Part of its popularity stems from its capacity to act as a direct physiological indicator of plant water status: meaning it does not rely on the availability of other forms of evidence (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…detectable irrigation infrastructure), and allows crop-specific inference of past water conditions. To date, the method has been applied in the Mediterranean, Near East, Central Europe and Britain, where it has been used to draw inferences on issues ranging from irrigation practices, crop yields, crop provenance and differential crop treatment, to climate change and climatic conditions at the emergence of agriculture (Aguilera et al, 2009, 2012; Araus et al, 2001, 2014; Bogaard et al, 2016; Ferrio et al, 2005; Fiorentino et al, 2012; Flohr et al, 2019; Lightfoot and Stevens, 2012; Masi et al, 2013; Riehl et al, 2008, 2014; Styring et al, 2016; Vaiglova et al, 2014; Wallace et al, 2015). This paper seeks to broaden the method’s applicability to monsoonal regions, by reporting a modern baseline study on barley ( Hordeum vulgare ) that has been grown in different soil and watering conditions in northwest India.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation